복강경 시술 환자에서 발생한 저체온증에 의한 Rocuronium의 근이완 회복 지연 - 류지근; 이병준; 양경아; 정욱 (Korean journal of anesthesiology, 2009)
Perioperative hypothermia can occur frequently and lead to various complications. Laparoscopic procedures do not require a large incision or exposure of the viscera, but a prolonged and high pressure procedure can lead to unexpected hypothermia. Hypothermia prolongs the time-course of non-depolarizing neuromuscular blocking agents by reducing the plasma clearance significantly. Rocuronium, a new aminosteroidal neuromuscular blocking agent, can be influenced by reductions in plasma clearance and prolong the duration of action. Therefore, patients must receive ventilator care in the ICU. Aggressive measures were taken for hypothermia, and the patient was discharged without any complications. We report a case of delayed of neuromuscular blockade by rocuronium in a hypothermic patient during a laparoscopic procedure with a brief review of literatures. Perioperative hypothermia can occur frequently and lead to various complications. Laparoscopic procedures do not require a large incision or exposure of the viscera, but a prolonged and high pressure procedure can lead to unexpected hypothermia. Hypothermia prolongs the time-course of non-depolarizing neuromuscular blocking agents by reducing the plasma clearance significantly. Rocuronium, a new aminosteroidal neuromuscular blocking agent, can be influenced by reductions in plasma clearance and prolong the duration of action. Therefore, patients must receive ventilator care in the ICU. Aggressive measures were taken for hypothermia, and the patient was discharged without any complications. We report a case of delayed of neuromuscular blockade by rocuronium in a hypothermic patient during a laparoscopic procedure with a brief review of literatures. KCI Citation Count: 0